A case report: 19-year-old male diagnosed with C1q nephropathy requiring renal replacement therapy - Randa Choueiri; Joelle Faddoul; Claude Ghorra; Jaqueline Al Najjar; Beatrice-Blondine Akiki; Sora Boustany; Vanessa Nseir (Open Exploration Publishing Inc., 2022)
C1q nephropathy is a rare glomerular disease. Clinical presentation is diverse and ranges from asymptomatic hematuria or proteinuria to symptoms and signs of nephrotic/nephritic syndrome. On light microscopy, it can be classified into two subtypes: minimal change disease (MCD)/focal segmental glomerulosclerosis (FSGS) group and immune complex mediated proliferative glomerulonephritis group. A case of a 19-year-old male patient presenting nausea and decreased appetite will be reported. The labs showed severe nephrotic syndrome and a progressive kidney injury over a few months that were never diagnosed. The immune workup came back negative. The patient mentioned that he was taking protein shakes a few months earlier for bettering his physical fitness. A renal biopsy was done and showed a major reduction in renal mass and C1q nephropathy. He received steroids without any improvement. He was started on hemodialysis afterward then got transplanted 8 months later. In front of this rapid deterioration, FSGS might be the underlying etiology rather than MCD. Further studies are warranted to establish a connection between protein supplements, and progression of kidney disease.